2022
DOI: 10.1107/s2059798322000092
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution structures of the bound effectors avadomide (CC-122) and iberdomide (CC-220) highlight advantages and limitations of the MsCI4 soaking system

Abstract: Cereblon (CRBN) is the substrate receptor of the CRL4CRBN E3 ubiquitin ligase and is a central player in targeted protein degradation. It is the target of the thalidomide-derived immunomodulatory drugs (IMiDs) and is one of the most widely employed receptors for proteolysis-targeting chimeras (PROTACs), both of which induce the ubiquitination and subsequent proteasomal degradation of target proteins. Structural studies of ligand binding to CRBN are crucial to elucidate the mechanisms of action and for mediatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…S3C) and have high B-factors in published x-ray structures. This observation, coupled with recently described alternative positions of these extended ligand groups (14), suggests that iberdomide's interaction with the sensor loop may be dynamic. It is likely that a more stable interaction with the sensor loop could be attained with next-generation CELMoD agents.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…S3C) and have high B-factors in published x-ray structures. This observation, coupled with recently described alternative positions of these extended ligand groups (14), suggests that iberdomide's interaction with the sensor loop may be dynamic. It is likely that a more stable interaction with the sensor loop could be attained with next-generation CELMoD agents.…”
mentioning
confidence: 60%
“…As with pomalidomide, in the presence of excess ligand, we observe density consistent with iberdomide within the glutarimide-binding pocket of both the CRBN closed and CRBN open conformers, suggesting that drug occupancy within CRBN is not responsible for the increased allosteric transition. Two prior crystal structures of the iberdomide-bound CRBN show that the additional phenyl and morpholino moieties of the iberdomide molecule can arch over the top of the sensor loop β-hairpin ( 13 , 14 ), a conformation that may aid in the stabilization of this structural motif. These data support our proposed allosteric model whereby enhanced ligand interaction with the sensor loop stabilizes the β-hairpin conformation, which promotes the closure of the TBD and Lon domains and ultimately translates to improved neosubstrate ubiquitination and subsequent degradation efficacy.…”
mentioning
confidence: 99%
“…CRBN E3 ligase modulators (CELMoDs), which are typically based on aminoglutarimide as the core binding moiety, [17][18][19][20][21] and to which examples such as iberdomide (CC-220, Figure 1) and mezigdomide (CC-92480) belong. 16,22,23 The structural elongation in iberdomide compared to lenalidomide enabled additional interactions with CRBN or ligase substrates leading to a more pronounced degradation of the CRBN neosubstrates, namely the transcription factors Ikaros (IKZF1) and Aiolos (IKZF3).…”
mentioning
confidence: 99%
“…SARs for CRBN binding have been investigated in detail by a series of studies using the thalidomide-binding domain of cereblon isoform 4 from Magnetospirillum gryphiswaldense (MsCI4). [73][74][75][76] In an early study, the uracil moiety of uridine was shown to fit in the thalidomide-binding pocket of MsCI4, albeit of lower affinity than thalidomide, suggesting that the minimal structure for CRBN binding is a cyclic imide. 73 Subsequently, detailed SARs were studied by fluorescence resonance energy transfer using MsCI4 and various cyclic imides and lactams.…”
Section: Structure-activity Relationships (Sars) Of Thalidomide-based...mentioning
confidence: 99%
“…2). 35,76 CC-885 is also structurally extended compared to the IMiDs class. As mentioned above, the urea moiety of CC-885 is located between E377 and H353 of CRBN and contributes to binding by hydrogen bonding to both side chains, while the methylchlorophenyl moiety is located close to GSPT1 domain 3 and probably contributes to the selective binding to GSPT1.…”
Section: Structure-activity Relationships (Sars) Of Thalidomide-based...mentioning
confidence: 99%